Perché la tecnologia ha bisogno dell’archeologia (Archeomatica, 2025)
Probably nothing more than technological development has characterized the last century. From research on cybernetics, which had an incredible momentum during the years of the Second World War, and that they involved the most brilliant mathematicians, psychologists and ethologists and physicists of the time, the technological development to support of contemporary society has practically none known setbacks. Every element of our daily life has been affected by this process which today still seems unstoppable: from communications to hygiene, from production to knowledge, from entertainment to ethics. Similarly, every discipline has been irremediably involved by technological and digital evolutions.